HUBUNGAN ANTARA PERSEPSI MAHASISWA TERHADAP DOSEN DENGAN MOTIVASI BELAJAR DI PROGRAM STUDI KEPERAWATAN UNIVERSITAS MUHAMMADIYAH SURAKARTA - Hana Rosiana Ulfah; Supratman Supratman (Jurnal Berita Ilmu Keperawatan, 2011)
Learning necessity on college students encourages their motivation from the inside, whereas the stimulus by lecturers encourages their motivation from the outside. In college students’ opinion, some nursing lecturers have not matched what they expect yet because they are less interesting and monotonous on giving the learning material, indiscipline or not on-time. Then most of the college students stated that those things also affected the learning motivation, because the college students became lazy to listen as well as study. Whereas the college students’ perception about good-figure of lecturer according to them was the ones who were kind, smile easily, good-looking, not weighing against them, on-time, easy to get a good mark from, not selfish, giving time outside the class to consult with, friendly and close in the learning process either inside or outside the class, able to give the learning material clearly and easy to understand as well as able to stimulate the college students’ learning motivation. The purpose of this research is to understand the relationship between college students’ perception towards nursing lecturers and learning motivation in nursing department of Muhammadiyah University of Surakarta. This research was analytic research with correlative approach. The population of this research was all active college students of Nursing Department of Muhammadiyah University of Surakarta year 2007-2010 whose total was 921 college students with 90 college students as sample. The used sample extraction technique in this research was proportionate stratified random sampling. Bivariate test using spearman rank showed that there was no significant relationship between college students’ perception towards lecturers and college students’ learning motivation (p = 0.454).